Occupational health and safety reports : a comparative study between Malaysia and the United Kingdom - Mara Ridhuan Che Abdul Rahman,; Mazni Yahya,; Maizatulakma Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Occupational health and safety reporting (OHS) is important for the evaluation of business risk as well as representing the commitment of the reporting companies to their stakeholders which in turn enhance companies’ images. The evidences of OHS reporting practices can be found in prior studies that exist in the literature of corporate social reporting, intellectual capital reporting and risk reporting. However not much can be understood from prior studies as the extent to which OHS index reporting captured was somewhat limited. Therefore, an exclusive OHS reporting study that apply more comprehensive index of reporting would ensure the far-reaching of its understanding. This index was applied in content analysis of corporate annual reports for financial year ended 2014. The objective of the study is to compare the practices of OHS reporting by 40 Malaysia companies against 40 companies from so-called reporting leading country such as the United Kingdom (UK). The findings are expected to be indicative of current practices of such reporting as well as to propose the area of improvement. In the absence of reporting guidelines, the study’s findings suggest that the OHS reporting practice in Malaysia is comparable to the UK. In some reporting items, Malaysia companies report even more than the UK companies. However, Malaysia companies are suggested to increase financial-based OHS reporting as they are behind their counterparts in the UK. This study is consistent with Stakeholder Theory where reporting companies not only perform OHS work as a mean to discharge its accountability but they also use annual reports as a method of accountability information conveyance.